(untitled) (Ibrahim Cardiac Medical Journal, 2021)
Background & objective: The aim of this study was to verify whether the ocular lens of type-2 diabetic retinopathy patients was thicker (measured by high resolution Ultrasonography) than those of non-diabetic individuals.The study also evaluated the differences in lens thickness (LT) between right and left eyes of diabetic retinopathy patients, and the differences in LT between proliferative and background retinopathy cases. Methods: This case-control study was conducted on 68 subjects (34 cases and 34 controls) aged 20-60 years in the Department of Radiology and Imaging, BIRDEM Hospital from March 2015 to February 2016. Adult patients suffering from type-2 diabetic retinopathy confirmed by slit-lamp examination were selected as cases, while apparently healthy subjects were taken as control. Patients with history of heart failure, ocular surgery, acute eye conditions, such as, conjunctivitis, scleritis, cataract or any other co-morbidities were excluded. Ocular mean lens thickness was measured by high resolution ultrasonography and was compared between case and control groups by Un-paired t-Test. Results: The study showed that type 2 diabetic patients had significantly thicker lenses than their non-diabetic counterparts (in right eye:case 4.1 ± 0.3 mm versus control 3.7±0.1 mm, p<0.001 and in left eye:case 4.2 ± 0.3 mm vs. control 3.7±0.1 mm, p<0.001). The study also revealed that proliferative retinopathy cases had thicker lenses than any other diabetic retinopathy groups (p < 0.05) and there was also statistically significant difference of HbA1c level between proliferative and background type II diabetic retinopathy cases (p<0.05) Conclusion: The study concluded that lens thickness is increased in type-2 diabetic retinopathy patients than that in non-diabetic healthy controls.The proliferative diabetic retinopathy cases possess thicker lens than the background retinopathy cases. Ibrahim Card Med J 2020; 10 (1&2): 40-44